THE INDO-PACIFIC REGION AS A GEOPOLITICAL "PIVOT" OF THE 21ST CENTURY - Hatidza, Berisa Alil (Political Review, 2024)
The subject of the paper refers to the analysis of the geostrategic importance of the Indo-Pacific region and the geopolitical movements and events in it at the beginning of the 21st century. The rise of China as a political, economic, and military power is the most important event in the transformation of the global international system, which, until recently, was sovereignly ruled by the USA. This geopolitical reality directed the world’s attention from the Euro-Atlantic to the Indo-Pacific region. In addition, the economic growth of the region, in inseparable synergy with political and military strategic interests, represents a major challenge to the long-standing US dominance in the Indo-Pacific region. The transformation of China into a regional power with global aspirations has changed the structure of regional relations, undermining the recently unquestioned American hegemony in this part of the world. The paper will focus on the basic geopolitical developments in the Indo-Pacific region, the new geopolitical “pivot” of the 21st century. The research used the content analysis method of the numerous relevant sources in which the Indo-Pacific region is considered, which includes a large expanse of water and land, where this specificity is reflected in the fact that the most significant “geopolitical game” today is related to the events in the waters of the South China Sea. The method of analysis and deduction in considering the character form and relationship of the rise of China as a political, economic, and military power and the events in the South China Sea indicate that the same could be the “maritime axis region” of the 21st century. Also, the method of synthesis and deduction was used in creating the most important views regarding the nature and manner of the mentioned connection and conditioning.